Looking at Male Violence - MacCormack, Terry (Canadian Journal of Counselling and Psychotherapy, 1996)
This article examines the three classes of theories traditionally used to explain the causes of male violence: physiological, psychological, and sociological. It argues that the search for such causes may in the long run be counterproductive, not only for the person who has been violated, but for the man who has committed the violence. A treatment approach is then suggested that helps the violent man to become both accountable and responsible for his violence. This involves inviting the man to consider not what appears to be causing his violent behaviour—something in himself, his background, or in his culture—but rather how these very forces might somehow be restraining him from acting respectfullv towards the people in his life.